A COMPARISON BETWEEN THE TWO CHARACTERS TOM BUCHANAN AND JAY GATSBY IN THE GREAT GATSBY BY F. S. FITZGERALD = SO SÁNH HAI NHÂN VẬT TOM BUCHANAN VÀ JAY GATSBY TRONG TÁC PHẨM GATSBY VĨ ĐẠI CỦA F. S. FITZGERALD - Trần, Nhật Linh (2020)
This paper involves comparing the two characters Tom Buchanan and Jay Gatsby on the basis of their social background, physical appearance, and personal characteristics. Hence, not only the similarities and differences between them but also the implications behind the depictions of Tom and Jay are revealed.